Postcolonial social dramas in European provincial towns: Frank Westerman's literary journalism. Issue 3 (4th May 2021) - De Capitani, Lucio
ABSTRACT: This article focuses on two literary reportages by Dutch writer Frank Westerman: El Negro en ik (2004; El Negro and me ) and Een woord een woord (2017; A word a word ), addressing postcolonial conflicts within provincial areas of Europe, seemingly alien to tensions about racism or the colonial past. In El Negro and me, the stuffed body of a 19th-century black man exhibited in a museum in a Catalan town becomes the centre of a controversy over his removal from display. In A word a word, a series of Dutch towns reveals a postcolonial presence in the form of South Moluccan terrorism. Using Victor Turner's concept of social drama – a public crisis that unveils the conflicts at work within a community – the article discusses Westerman's reframing of these provincial spaces within (post)colonial history. Both works, while discussing conflicts that are distant, geographically or temporally, from present-day Netherlands, intervene in contemporary Dutch debates on multiculturalism and inclusion.